2017
DOI: 10.18172/cig.3235
|View full text |Cite
|
Sign up to set email alerts
|

Timing and extent of late pleistocene glaciation in the arid Central Andes of Argentina and Chile (22°-41°S)

Abstract: ABSTRACT. The arid Central Andes are a key site to study changes in intensity and movement of the three main atmospheric circulation systems over South America: the South American Summer Monsoon (SASM), the Westerlies and the El Niño Southern Oscillation (ENSO). In this semi-arid to arid region glaciers are particularly sensitive to precipitation changes and thus the timing of past

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 51 publications
3
56
1
2
Order By: Relevance
“…5). Glaciers advanced in nearby parts of the southern Central Andes around this time, for example the Nevado de Chañi (24°S; Martini et al, 2017) and the Sierra de Quilmes (26°S; Zech et al, 2017), as well as farther north at the Chajnantor plateau (23°S; Ward et al, 2015;, Uturuncu volcano (22°S; Blard et al, 2014;Ward et al, 2017), and the Cordillera Huayhuash in Peru (10°S; Hall et al, 2009). We therefore infer that the M1 advance at the Sierra de Aconquija occurred within a more widespread wet period in the Central Andes, corresponding to the summer insolation maximum around 40-45 ka, during which the SASM was intensified.…”
Section: Moraine Unit M1mentioning
confidence: 99%
See 1 more Smart Citation
“…5). Glaciers advanced in nearby parts of the southern Central Andes around this time, for example the Nevado de Chañi (24°S; Martini et al, 2017) and the Sierra de Quilmes (26°S; Zech et al, 2017), as well as farther north at the Chajnantor plateau (23°S; Ward et al, 2015;, Uturuncu volcano (22°S; Blard et al, 2014;Ward et al, 2017), and the Cordillera Huayhuash in Peru (10°S; Hall et al, 2009). We therefore infer that the M1 advance at the Sierra de Aconquija occurred within a more widespread wet period in the Central Andes, corresponding to the summer insolation maximum around 40-45 ka, during which the SASM was intensified.…”
Section: Moraine Unit M1mentioning
confidence: 99%
“…Prior works identified anomalously old outliers on the grounds that they (i) sit far away from age clusters (e.g., Martini et al, 2017); (ii) violate the local stratigraphic order (e.g., Bromley et al, 2016;Ward et al, 2017;Zech et al, 2017); (iii) can be identified by statistical testing (e.g., Smith et al, 2005a,b;Jomelli et al, 2011);or (iv) by field observations that suggest a particular boulder is significantly older or was derived from hillslope debris (e.g., Martin et al, 2018).…”
Section: Nuclide Inheritancementioning
confidence: 99%
“…La evolución de éstos glaciares se corresponde con otros estudios para los Andes Centrales (Espizua 1999(Espizua , 2002(Espizua y 2004Moreiras et al, 2016) y en general en la cordillera de los Andes (Ackert, et al 2008;Glasser, et al 2008;Martinez et al, 2011;Martini et al, 2017;Rabassa et al, 2011;Ward et al, 2017;Zech et al, 2017;Vargo et al, 2018), habiéndose identificado en diversos depósitos morrénicos de los Andes Áridos los eventos del Último Máximo Glacial y el Tardiglaciar (Moreiras et al, 2016y Martini et al, 2017.…”
Section: Discussionunclassified
“…Las glaciaciones ocurridas durante el periodo Cuaternario, han modelado intensamente el relieve actual de la cordillera de los Andes (Ackert, et al 2008;Glasser, et al 2008;Martinez et al, 2011;Martini et al, 2017;Ward et al, 2017;Zech et al, 2017;Vargo et al, 2018). Durante el Pleistoceno (2,58 a 0,0117 Ma) y Holoceno (desde hace 11,700 ka antes del presente, BP) han ocurrido diversos eventos de descenso de temperatura y avances de los frentes de hielo glacial.…”
Section: Introductionunclassified
“…The local last glacial maximum ice extension is thought to have occurred prior to the global Last Glacial Maximum (LGM, ca . 35–40 kyr); however, no LGM glacial reconstruction is yet available for the study area. The headwaters of the Santa Cruz, Mondaca and Pachón valleys were covered by Pleistocene valley glaciers, based on the observed presence of erosive forms and glacial deposits over all the main valleys and subordinated creeks (Figure ).…”
Section: Study Areamentioning
confidence: 99%